Stenopodidean shrimps (Crustacea: Decapoda) from New Caledonian waters - Goy, Joseph W. (Zootaxa, 2015)
A small collection of 159 specimens of stenopodidean shrimps from New Caledonian waters has been studied and found to represent 13 species in 6 genera, adding 8 new species of stenopodideans to the Southwest Pacific fauna. Two new species are recognized, Richardina crosnieri n. sp. and Spongiocaris neocaledonensis n. sp. Two species of Odontozona are redescribed. Illustrations are provided for all 13 species. Association with host hexactinellid sponges is verified for some of the commensal spongicoloids, and the first association of a stenopodidean shrimp with a gorgonian is reported. Bathymetric ranges are extended for the infraorder, as well as at the generic and specific levels.